Work-Life Balance: An Inhibiting or Supporting Employee Engagement on Performance? - Patricia Nia Sari Damanik (Journal Of Management Analytical and Solution (JoMAS), 2025)
In an increasingly competitive business environment, employee engagement hasbecome a crucial factor in determining the success of an organization.Employees who are actively engaged in their work demonstrate higher levels ofproductivity, stronger innovation, and greater loyalty to the organization.However, the main challenge currently faced is how to ensure that employeeengagement can effectively improve performance. One of the factors that canmoderate this relationship is work-life balance, which plays an important role inmaintaining employee well-being while also improving employee performanceat the North Sumatra Provincial Statistics Office (BPS). This study explores therole of work-life balance as a moderating variable that affects employeeengagement on performance using a descriptive quantitative approach. Theresearch population consists of 111 employees of the North Sumatra ProvincialStatistics Office using a saturated sampling technique. Data collectiontechniques were carried out through questionnaires and structured interviews.Data were analyzed using descriptive analysis, reliability and validity tests, aswell as Partial Least Squares Structural Equation Modeling (PLS-SEM). Theresearch results prove that employee engagement has a positive and significantimpact on employee performance. However, work-life balance hinders theimpact of employee engagement on employee performance.